A Decade of Data: Findings from the first 10 years of Footprints in Time, 2020 - Department of Social Services (Department of Social Services, 2021)
The report includes information about what has changed for families since the interviews first started, racism and discrimination, Aboriginal and Torres Strait Islander language at home and at school, school engagement, sleep, diet, exercise, dental health and how teaching Indigenous history and culture is associated with better literacy and numeracy.
Keywords: Adolescents and youth; Disadvantage, adversity and resilience; Childhood and child development; Culture and language; Families and relationships; Health and wellbeing; Income, wealth and finances; Lifestyle